2020
DOI: 10.2139/ssrn.3555762
|View full text |Cite
|
Sign up to set email alerts
|

Robust Minimal Instability of the Top Trading Cycles Mechanism

Abstract: In the context of priority-based resource allocation, we formulate methods to compare assignments in terms of their stability as binary relations (on the set of possible assignments) that depend on the preference and the priority profile. We introduce three basic properties, stability preferred, separability, and consistency, that a reasonable stability comparison should satisfy. We show that, for any stability comparison satisfying the three properties, the top trading cycles (TTC) mechanism is minimally unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Yet, Abdulkadiroglu et al (2020) has shown that if we fix a set of agents and a set of schools with unit capacities, then TTC is minimally unstable among efficient and strategy-proof mechanisms. In our companion paper Dogan and Ehlers (2020b), we show that TTC is also minimally unstable among efficient and strategy-proof mechanisms for any of our stability comparisons if we fix a set of agents and a set of schools with unit capacities.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Yet, Abdulkadiroglu et al (2020) has shown that if we fix a set of agents and a set of schools with unit capacities, then TTC is minimally unstable among efficient and strategy-proof mechanisms. In our companion paper Dogan and Ehlers (2020b), we show that TTC is also minimally unstable among efficient and strategy-proof mechanisms for any of our stability comparisons if we fix a set of agents and a set of schools with unit capacities.…”
Section: Discussionmentioning
confidence: 91%
“…8 Not all conclusions have to be sensitive, however. InDogan and Ehlers (2020b), we show that a result byAbdulkadiroglu et al (2020), which relies on a particular stability comparison method, is, in fact, robust to the choice of the stability comparison method.…”
mentioning
confidence: 90%
“…Yet, Abdulkadiroğlu et al (2020) has shown that if we fix a set of agents and a set of schools with unit capacities, then TTC is minimally unstable among efficient and strategy‐proof mechanisms. In our companion paper Doğan and Ehlers (2020b), we show that TTC is also minimally unstable among efficient and strategy‐proof mechanisms for any of our stability comparisons if we fix a set of agents and a set of schools with unit capacities.…”
Section: Discussionmentioning
confidence: 92%
“… Not all conclusions have to be sensitive, however. In Doğan and Ehlers (2020b), we show that a result by Abdulkadiroğlu et al (2020), which relies on a particular stability comparison method, is, in fact, robust to the choice of the stability comparison method. …”
mentioning
confidence: 95%
“…When mechanisms do not perfectly satisfy a property of interest, another approach consists in comparing them using a criterion formalizing "by how much" each solution violates the property. In the case of stability, which requires the absence of blocking pairs, Combe et al (2017), Abdulkadiroglu et al (2019), Dogan and Ehlers (2020b) and Bonkoungou and Nesterov (2020) compare mechanisms by measuring, in different ways, the number of blocking pairs or the number of players participating to a blocking pair in each profile. Dogan and Ehlers (2020a) axiomatically characterize criteria for stability comparisons based on axioms specific to this property.…”
Section: Related Literaturementioning
confidence: 99%